The classification of synusial epigeic and epiphytic bryophyte communities of forest coenoses of forest-steppe zone of Ukraine - Gapon, Svetlana (Biodiversity: Research and Conservation, 2012)
The syntaxonomical classification and characteristics of synusial epigeic and epiphytic bryophyte communities of forest coenoses of forest-steppe zone of Ukraine is presented in this paper.